GEOQUÍMICA DO SISTEMA LACUSTRE CARBONÁTICO APTIANO DA BACIA DO JATOBÁ, NORDESTE DO BRASIL - Rocha, Dunaldson Eliézer Guedes Alcoforado; Lima, Rafael Pereira; Varas, José Diego Dias; de Moraes, Alex Souza; Barbosa, José Antônio; Miranda, Tiago Siqueira; Neumann, Virgínio Henrique de Miranda Lopes (Geochimica Brasiliensis, 2017)
This paper presents analyses of C and O isotopes and results of X-ray diffractometry in carbonate and terrigenous rocks of the Aptian lacustrine system of Serra Negra, Jatobá basin, northeastern Brazil. The carbonates were analyzed from samples collected from logs of well and outcrops. Thin sections were studied and have been shown that the carbonate succession are composed by mudstones, wackstones and packstones, ranging from light beige to dark brown in color, with framboidal pyrite. Analyses of C and O isotopes were conducted in 113 samples. The δ13C values ranged from -8.72 to 2.47 ‰ VPDB and δ18O values presented values between -8.67 to -3.96 ‰ VPDB. These values show good correlation with those obtained in other studies for lacustrine carbonates. Based on these results it is proposed here that the carbonates of Serra Negra were deposited in a hydrologically closed paleolake. The X-ray difractograms showed illite and smectite as dominant clay minerals in laminated limestones, shales, aswell as in sandstones lithofacies.